Extensively-drug-resistant Klebsiella pneumoniae ST307 outbreak strain from north-eastern Germany does not show increased tolerance to quaternary ammonium compounds and chlorhexidine. (July 2021) - Hornschuh, M.; Zwicker, P.; Kramer, A.; Schaufler, K.; Heiden, S.E.; Bohnert, J.A.; Becker, K.; Hübner, N-O.
Summary: Background: An outbreak of extensively-drug-resistant Klebsiella pneumoniae strain ST307 in a cluster of hospitals in north-east Germany gave rise to the assumption that the epidemiological success of the strain could be based on increased tolerance to biocides. Methods: The tolerance of the outbreak strain was compared with epidemiologically unrelated clinical isolates of K. pneumoniae, and reference strains of Pseudomonas aeruginosa (ATCC 15442) and Escherichia coli K12 (NCTC 10538). Tests were performed in a miniaturized assay based on European Standard EN 1040. The widely used biocides benzalkonium chloride (BAC) and didecyl dimethyl ammonium chloride (DDAC), their commercial formulation Descosept spezial (DS), and the antiseptic agent chlorhexidine digluconate (CHG) were selected as test substances. These biocides are used regularly in the hospitals involved in the outbreak. Findings: All biocides had a bactericidal effect against all tested strains in the quantitative suspension test within 5 min at typically used concentrations and dilutions. The effectiveness of BAC and DDAC alone and in combination, and CHG antisepsis were not impaired under tested conditions. Conclusion: The outbreak strain did not show significantly increased tolerance towards biocides regarding the antiseptic. Thus, the epidemiological success of the strain has to be ascribed to other causes, such as inadequate hand hygiene of visitors.